Towards universal health coverage: Exploring healthcare-related financial risk protection for the informal sector in Kenya - Okungu, Vincent Okongo (Health Economics Unit, 2016)
There is a global emphasis to move towards universal health coverage (UHC) with the goal of making health services more equitable and accessible for all, without the risk of financial catastrophe when paying for the services. A key element of UHC reforms is to move away from out-of-pocket payments for health services towards a greater emphasis on mandatory prepayment health financing. The main challenge for low- and middle-income countries is how to extend coverage for informal sector populations, which in most cases are disproportionately exposed to catastrophic and impoverishing healthcare costs. This study explored the nature of the informal sector in Kenya, the experience of members of the informal sector with the health system, their views on different prepayment mechanisms for health services and compares the resource requirements for UHC through a system that requires contributions from the informal sector and a system that is non-contributory.